PEMBINAAN EKSTRAKURIKULER MAPSI DAN OSN SEBAGAI WADAH PENGEMBANGAN POTENSI, PRESTASI, DAN KARAKTER RELIGIUS SISWA - Melviyana, Elka; Mardiyah, Aulia; Luthfinda, Muhammad; Famularsih, Sari; Hanik, Umi; Prihananto, Agus (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This community service activity aims to strengthen the implementation of extracurricular coaching in Islamic Subject and Arts (MAPSI) and the National Science Olympiad (OSN) as platforms for developing students’ potential, achievements, and religious character at SMP Negeri 4 Salatiga. The program was carried out collaboratively between supervising teachers and MBKM Teaching Assistance students from UIN Salatiga using a participatory and school-based approach. The activities included stages of coordination, coaching, mentoring, and evaluation conducted regularly every week. MAPSI coaching focused on developing students’ talents in Cerdas Cermat Islami (CCI), Tartil, Tilawah, Tahfidz, and Rebana, while OSN coaching emphasized analytical and problem-solving skills in mathematics and science through intensive practice. The results showed a significant improvement in students’ discipline, confidence, and enthusiasm for learning. Participation levels reached 95%, and several students achieved awards in city-level competitions. The collaboration between the university and the school successfully fostered an integrated model of religious character education and academic achievement development. ABSTRAK Kegiatan pengabdian masyarakat ini bertujuan untuk memperkuat pelaksanaan pembinaan ekstrakurikuler Mata Pelajaran dan Seni Islami (MAPSI) serta Olimpiade Sains Nasional (OSN) sebagai wadah pengembangan potensi, prestasi, dan karakter religius siswa di SMP Negeri 4 Salatiga. Program ini dilaksanakan secara kolaboratif antara guru pembina dan mahasiswa MBKM Asistensi Mengajar UIN Salatiga melalui pendekatan partisipatif berbasis sekolah. Kegiatan meliputi tahap koordinasi, pembinaan, pendampingan, serta evaluasi yang dilakukan secara rutin setiap minggu. Pembinaan MAPSI berfokus pada pengembangan bakat siswa dalam bidang Cerdas Cermat Islami (CCI), Tartil, Tilawah, Tahfidz, dan Rebana, sedangkan pembinaan OSN menekankan kemampuan analisis dan pemecahan masalah siswa melalui latihan intensif di bidang Matematika dan IPA. Hasil kegiatan menunjukkan peningkatan yang signifikan pada kedisiplinan, kepercayaan diri, dan semangat belajar siswa. Tingkat partisipasi mencapai 95%, serta beberapa siswa berhasil meraih prestasi di ajang lomba tingkat kota. Kolaborasi antara perguruan tinggi dan sekolah ini berhasil menciptakan model pembinaan terpadu yang mampu mengembangkan prestasi akademik sekaligus karakter religius peserta didik.